The impact of low muscle function on health-related quality of life in Indonesian women with systemic lupus erythematosus. (April 2021) - Sumantri, Stevent; Rengganis, Iris; Laksmi, Purwita Wijaya; Hidayat, Rudy; Koesnoe, Sukamto; Shatri, Hamzah
Objective: There was no study aimed at evaluating the effect of muscle function on SLE patients' quality of life using the Sarcopenia Quality of Life (SarQoL) questionnaire. Methods: This cross-sectional study recruited 61 women with SLE consecutively, muscle function was measured with Jamar handheld-dynamometer and 6-meter walk test, HRQoL was measured with Sarcopenia Quality of Life (SarQoL) questionnaire. The cut-off point for low muscle strength (<18 kg) and low gait speed (<1.0 m/s) was according to the Asian Working Group on Sarcopenia 2019 criteria. Statistical analysis was conducted with a t-test for mean difference, and linear regression was used to adjust confounders (age, protein intake, physical exercise, and disease activity). Results: The subjects' mean muscle strength was 19.54 kg (6.94), and 44.3% (n = 27) was found to have low muscle strength. The subjects' mean gait speed was 0.77 m/s (0.20), and 90.3% (n = 55) was found to have low gait speed. The difference of total SarQoL score in subjects with normal and low muscle strength was found to be significant; 74.86 (9.48) vs. 65.49 (15.51) (p = 0.009), and still statistically significant after adjustments with age, protein intake, physical exercise level, and disease activity [B 0.56; 95% CI 0.08–1.03; p = 0.022]. The difference of total SarQoL score in subjects with normal and low physical performance was found to be not significant, 70.67 (11.08) vs. 70.72 (13.56) (p = 0.993). Conclusion: There was a significant difference in SarQoL's total score in normal compared with low muscle strength groups of Indonesian women with SLE.